Motivating organizational commitment in hotels: The relationship between leaders and employees. Issue 4 (1st October 2016) - Chiang, Chun-Fang; Lin, Ming-Yu
ABSTRACT: This study developed and tested a research model, which predicted the impacts of justice (procedural and interactive justice), trust (cognitive and affective trust), and leader–member exchange between transformational leadership and organizational commitment. Respondents were full-time employed frontline employees of international hotels of Taiwan. The results demonstrated that justice, trust, and leader–member exchange are mediators between transformational leadership and organizational commitment. The results also show that transformational leadership had a positive relationship with justice and trust. Further, justice and trust had a positive relationship with leader–member exchange, and partially mediated the relationship between transformational leadership and leader–member exchange. Leader–member exchange significantly and positively influenced organizational commitment, and partially mediated the relationship between justice and trust and organizational commitment. As such, hotel managers should endeavor to have transformational leadership to facilitate greater justice and trust between employees and supervisors in order to achieve improved leader–member exchange then increased organizational commitment.